Apakah Terdapat Perilaku Cyberbullying Pada Pengguna Media Sosial Instagram? - Akbar, Fathur Ramadhan; Sedjo, Praesti (Arus Jurnal Pendidikan, 2026)
Cyberbullying behavior among Instagram users can lead to depression, anxiety, low self-esteem, and even suicidal thoughts in victims. The purpose of this study is to describe and analyze cyberbullying behavior among Instagram users. The data analysis technique used in this study was descriptive statistical analysis. The sample size for this study was 15 respondents who actively use Instagram. The results showed that Instagram users exhibited low levels of cyberbullying behavior. Overall, the subjects in this study obtained an empirical mean score of 99.91, which is in the low category. The results were analyzed descriptively based on gender, age, occupation, highest level of education, monthly income, number of followers, number of followings, duration of Instagram use, duration of Instagram use, and the number of Instagram accounts followed. This may be due to the subjects' increasing awareness of the causes and consequences of cyberbullying behavior and their awareness of fostering positive interactions with other social media users.